STUDY OF THE RANGE AND TECHNOLOGICAL FEATURES OF THE DERUFA DECODER SERIES FOR WALL DECORATION IN A MODERN INTERIOR - OLIJNYK, Halina; DANCHENKO, Yuliya; KORNYTSKA, Larysa; RASTORHUIEVA, Mariia (Herald of Khmelnytskyi National University. Technical sciences, 2023)
The use of the products of the well-known German brand - DERUFA DecoDer series in decorative wall decoration in a modern interior gives unlimited opportunities for one's creativity and unique design. The range of products presented on the domestic market is distinguished by a wide range of colors, various environmental, operational, and technological characteristics, etc. Water-dispersed acrylic paints, decorative coatings, primers, and other DERUFA products of the DecoDer series offer unique innovative solutions with high-quality characteristics, focused on each client, following current market trends in the field of interior design and design. The available information about the finishing materials intended for wall decoration in modern interiors and represented by the DERUFA DecoDer series of products is insufficient and needs more clarification.The work presents the results of research related to the identification of the features of DERUFA products of the DecoDer series. The use of DERUFA water-dispersed acrylic paints of the DecoDer series has the following advantages: no smell when applying the paint to the wall, quick drying of the paint, and resistance to abrasion and moisture. Such paints are environmentally friendly and aesthetically attractive. DERUFA water-dispersed acrylic wall paints of the professional DecoDer series can be used together with decorative coatings, which are produced separately and can be applied to the painted surface to obtain a decorative relief coating on the wall surface in a modern interior. Such a coating is produced with various fillers imitating the effects of polished marble, velvet, suede, etc. To enhance the decorative effect, special primers of the DecoDer DERUFA series are used, the application of which, if a certain technology is followed, enhances the decorative effect. STUCCO PENELLO and STUCCO RILEVATO primers can be applied without restrictions on any mineral bases: plaster, brick, or plasterboard. However, it is not allowed to apply a primer on surfaces made with lime plaster, as well as on surfaces previously painted with oil, alkyd, or silicate paints. The primer is applied to the surface of the wall with a roller, and then the necessary relief of the surface is provided with a brush. To create relief, it is recommended to use chaotic cross-shaped or semicircular movements and special techniques. To add special decorative effects, it is possible to apply the material with a spatula or trowel. If you want to get a deeper relief, it is recommended to apply the material in two stages. POLICROMO BRILLIANTE primer can be applied with a brush, roller, sponge, or spatula on previously painted surfaces, except those painted with oil, alkyd, and silicate paints. When applying to the surface using a roller, the primer is first evenly distributed over the surface, and later the necessary effects are created using a spatula or brush. In addition, it is recommended to apply the material in limited areas to avoid its drying before the decoration begins.Thus, the considered studies presented in this work allow us to identify features related to the technological and operational capabilities of DERUFA products of the DecoDer series. The considered information is important for organizing the informative market.
Keywords: wall decoration; modern interior; technological characteristics; operational capabilities; DERUFA products of the DecoDer series; water-dispersed acrylic paints; decorative coatings; primers